1986
DOI: 10.1002/aja.1001760306
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and vascular anatomy of the accessory respiratory organs of the air‐breathing climbing perch, Anabas testudineus (Bloch)

Abstract: The vascular organization and endothelial cell specialization of the air-breathing organs of Anabas testudineus were examined by light and scanning electron microscopy of fixed tissue and vascular corrosion replicas. The vessels supplying blood to the lining of paired suprabranchial chambers and the plicated labyrinthine organs within the chambers are tripartite, having a median artery and paired, lateral veins. Hundreds of respiratory islets, the functional units of gas exchange, cover the surfaces of both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…The physiological significance of this separation depends upon the ability of the heart and central vessels to minimize the mixing of venous return from the systemic and accessory respiratory organs. (A detailed account of the vascular connections between the heart, gills, and accessory air-breathing organs can be found in Munshi et al, 1986). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological significance of this separation depends upon the ability of the heart and central vessels to minimize the mixing of venous return from the systemic and accessory respiratory organs. (A detailed account of the vascular connections between the heart, gills, and accessory air-breathing organs can be found in Munshi et al, 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Oxygenated blood from the air-breathing organs returns directly to the heart through short, largebore jugular veins that empty into the ductus Cuvieri. There appears to be relatively little opportunity for mixing of venous blood from the air-breathing organs with the systemic venous blood in the jugular veins (Munshi et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Hughes and Munshi (1979) observed that lamellae of Heteropneustes fossilis were also covered with microvilli, whereas Rajbanshi (1977) reported that this fish has microridges on its lamellar surface. The respiratory surfaces of other bimodal breathing fish are also modified; microridges and microvilli are completely absent from the smooth ARO respiratory epithelium of Anabas testudineus and Monopterus cuchia (Munshi et al, 1986. While the transition from microridges to a microvillous or smooth respiratory epithelium may be correlated with some property of epithelial function, it is doubtful if this is solely a n adaptation for bimodal breathing.…”
Section: Surface Ultrastructurementioning
confidence: 94%
“…It possesses a special accessory breathing organ (ABO), situated just above the gills in a large extension on the upper part of each gill chamber, which facilitates the utilization of atmospheric air (Graham, 1997). The ABO is composed of lamellae which are covered with an extremely vascular layer of skin and convoluted into numerous folds to maximize the surface area for respiration (Hughes and Munshi, 1973;Munshi et al, 1986). Because the ABO structure resembles a complicated maze, it has been dubbed the labyrinth organ.…”
Section: Introductionmentioning
confidence: 99%